Urgensi Sema No.3/2023 dalam Menghindari Penggunaan Kepailitan Sebagai Alat Penagihan Utang: Analisis Putusan PKPU dan Implikasi terhadap Prinsip Pembuktian Sederhana: Studi Kasus: Putusan Nomor 97/Pdt.Sus-Pkpu/2024/Pn. Niaga Jakarta Pusat dan Putusan Nomor 71/Pdt.Sus-Pkpu/2024/Pn. Niaga Jkt Pusat - Mella Novianti (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The use of bankruptcy as a debt collection tool has become a significant issue within the Indonesian bankruptcy law system. The fundamental principle should be that bankruptcy serves as a collective solution for debtors unable to pay their debts to creditors, rather than a coercive instrument to force a debtor to settle a specific debt. However, in practice, there are instances of misuse where bankruptcy petitions are filed by a single creditor or a group of creditors with the primary objective of pressuring the debtor for immediate payment, even when the debtor still possesses financial capacity. This situation threatens the balance between debtor protection and creditor rights.This research is normative legal research utilizing a case study approach. Normative legal research is employed to examine prevailing norms, principles, and legal rules, specifically the Law on Bankruptcy and Suspension of Obligation for Payment of Debts (UUKPKPU), Supreme Court Circular Letter (SEMA) No.3/2023 and legal doctrines related to bankruptcy. The case study approach is applied through an in-depth analysis of Decision Number 97/Pdt.Sus-PKPU/2024/PN Niaga Jakarta Pusat and Decision Number 71/Pdt.Sus-PKPU/2024/PN Niaga Jakarta Pusat. The analysis of these decisions indicates that the panel of judges applied the principle of prudence as mandated by SEMA No.3/2023. In their considerations, the panel did not merely rely on the formal requirements of simple evidence but also conducted a substantial verification of the existence of the debt and the number of creditors. The judges rejected the PKPU (Suspension of Debt Payment Obligations) petitions on the grounds that the submitted debts were still in dispute (disputed debt) and did not constitute mature and collectible debts (liquidated debt). The implications of these decisions are highly significant.